Clostridium difficile Infection and Proton Pump Inhibitor Use in Hospitalized Pediatric Cystic Fibrosis Patients. (15th November 2011) - Pohl, John F.; Patel, Raza; Zobell, Jeffery T.; Lin, Ellen; Korgenski, E. Kent; Crowell, Kody; MacKay, Mark W.; Richman, Aleesha; Larsen, Christian; Chatfield, Barbara A.
Abstract : Children with cystic fibrosis (CF) often take proton pump inhibitors (PPIs), which helps improve efficacy of fat absorption with pancreatic enzyme replacement therapy. However, PPI use is known to be associated with Clostridium difficile -( C. diff -) associated diarrhea (CDAD). We retrospectively evaluated the incidence of C. diff infection from all pediatric hospital admissions over a 5-year period at a single tertiary children's hospital. We found significantly more C. diff -positive stool tests in hospitalized patients with CF compared to patients with no diagnosis of CF. However, use of a PPI was not associated with an increased risk of CDAD in hospitalized CF patients. In summary, C. diff infection is more common in hospitalized pediatric CF patients although PPI use may not be a risk factor for CDAD development in this patient population.